MENINGKATKAN AKTIVITAS BELAJAR BAHASA INGGRIS PADA SISWA KELAS VII-A SMP NEGERI 2 SINUNUKAN MELALUIEFEKTIFITAS MODEL PEMBELAJARAN TIME TOKEN - Wansari Eviyanti (Universitas Negeri Medan, 2017)
Abstract: Improving the Learning Activities of English in Grade VII-A Students of SMP Negeri 2 Sinunukan through Effectiveness of Time Token Learning Model. This study aims to see learning activities and student learning outcomes. The subject of this study is 23 people. The learning result test pretes, with an average of29.9.Test results of Formative Study I and Formative II results respectively show 73.3 and 83.3. Seeing the data there are changes and changes caused by teacher actions during KBM in Cycle II. Student activity data according to observer observation in Cycle I, among others, write / read (43%), work on LKS (23%), ask fellow friends (11%), ask teachers (9%), and irrelevant to KBM (14 %). Student activity data according to observation in Cycle II, among others, write / read (26%), work on LKS (46%), ask fellow friends (14%), ask teachers (8%), and irrelevant to KBM (6% ). Implementation of Time Token learning model during KBM students are very happy, very enthusiastic, and researchers / teachers before group need to explain the purpose of grouping so that students understand their respective duties. Keywords: Learning Activity, Time Token Learning Model Abstrak : Meningkatkan Aktivitas Belajar Bahasa Inggris Pada Siswa Kelas VII-A SMP Negeri 2 Sinunukan Melalui Efektifitas Model Pembelajaran Time Token. Penelitian ini bertujuan untuk melihat aktivitas belajar dan hasil belajar siswa. Subjek penelitian berjumlah 23 orang. Tes hasil belajar pretes, dengan data rata-rata 29,9. Tes hasil belajar Formatif I dan Formatif II hasilnya masing-masing menunjukkan 73,3 dan 83,3. Melihat data tersebut ada perubahan dan perubahan tersebut akibat tindakan guru selama KBM pada Siklus II.Data aktivitas siswa menurut pengamatan pengamat pada Siklus I antara lain menulis/membaca (43%), mengerjakan LKS (23% ), bertanya sesama teman (11%), bertanya kepada guru (9%), dan yang tidak relevan dengan KBM (14%). Data aktivitas siswa menurut pengamatan pada Siklus II antara lain menulis/membaca (26%), mengerjakan LKS (46%), bertanya sesama teman (14%), bertanya kepada guru (8%), dan yang tidak relevan dengan KBM (6%). Kata Kunci : Aktivitas Belajar, Model Pembelajaran Time Token